Corporate Governance in Japan 2007
DOI: 10.1093/acprof:oso/9780199284511.003.0002
|View full text |Cite
|
Sign up to set email alerts
|

2 Relationship Banking in Post‐Bubble Japan: Coexistence of Soft‐ and Hard‐Budget Constraints

Abstract: This chapter examines the changes in the Japanese main banking system. Despite the deregulation of bond markets in the mid-1990s, the overall dependence of firms on bank borrowing increased rather than decreased among listed firms during the 1990s. Large firms lessened their ties with banks and began financing through bonds, yet smaller listed firms continued borrowing from banks. In particular, firms with previously high levels of bank debt relied on their main bank for an increasing proportion of those loans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…In the worst cases, the main banks might abandon any attempt to rescue their borrowing firms and instead choose to liquidate them. This disciplinary mechanism differs from the Anglo‐American (market‐oriented) system based on takeovers and bankruptcy procedures (Arikawa and Miyajima, ).…”
Section: Prior Studies and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the worst cases, the main banks might abandon any attempt to rescue their borrowing firms and instead choose to liquidate them. This disciplinary mechanism differs from the Anglo‐American (market‐oriented) system based on takeovers and bankruptcy procedures (Arikawa and Miyajima, ).…”
Section: Prior Studies and Hypothesis Developmentmentioning
confidence: 99%
“…In Japan, there are stable shareholders that are highly concentrated among the corporate stockholders with financial institutions. In this case, firms are closely connected; they affect each other through cross-holdings of equity ownership, and generally depend on a large commercial bank (i.e., the main bank) for their primary banking needs (Hoshi et al, 1990(Hoshi et al, , 1991Aoki and Patrick, 1994;Douthett and Jung, 2001;Arikawa and Miyajima, 2007;Shuto and Kitagawa, 2011). 1 One of the important features about the stable shareholding arrangements made through cross-shareholdings and financial institutions is the implicit long-term contracts among them.…”
Section: Introductionmentioning
confidence: 99%
“…However, bank troubles in the 1990s heavily affected the role of main banks. According to Arikawa and Miyajima (2005), main bank commitment to client firms played contrasting roles in this period. Exploiting their superior positions to client firms, main banks tended to impose employment reduction on firms maintaining their earnings (short-termism based on an extension of hard budgeting).…”
Section: Multivariate Regression Of Debt Choicementioning
confidence: 99%
“…In fact, using data for the 1998 fiscal year, Hori and Osano (2002) find that firms with weaker prospects and a greater likelihood of suffering financial distress relied more on main bank loans. Similarly, Arikawa and Miyajima (2006) found that firms with low growth opportunities increased their reliance on bank loans in the 1990s. Why would banks have increased loans to some of the weakest firms?…”
Section: Post-bubble Evidencementioning
confidence: 95%
“…However, the fact that the performance of firms with close ties to their main bank suffered is somewhat puzzling, insofar as it appears that many firms increased their reliance on bank loans during the latter half of the 1990s, even as the bond market had been deregulated (for example, Peek and Rosengren 2005;Arikawa and Miyajima 2006). In fact, using data for the 1998 fiscal year, Hori and Osano (2002) find that firms with weaker prospects and a greater likelihood of suffering financial distress relied more on main bank loans.…”
Section: Post-bubble Evidencementioning
confidence: 99%